Disponibilidade de alimentos segundo a classificação nova: características de um município de acesso remoto no interior do Amazonas - Cunha, Andreza Bruce (Brasil, 2024)
Introduction: The food environment is a decisive factor in defining healthy food choices, especially in the most vulnerable population. Studies focusing on mapping food supply in neighborhoods, communities and municipalities have been relevant in the search to understand to what extent the characterization of these environments is being decisive in food choices and, consequently, in the nutritional and health profile of the population. The foods chosen to be investigated in the establishments were classified according to the NOVA classification. Additionally, the Brazilian Population Food Guide provided a detailed description of food types. Objective: Describe the availability and types of establishments that sell food, using the NOVA classification, adopted by the Food Guide for the Brazilian Population, in a municipality in the interior of the state of Amazonas (Brazil) Methods: This is an transverse study, with an on-site search to collect data. In this way, establishments that sold food in 16 different neighborhoods were identified, classifying them by type. A total of 117 establishments were visited, out of a total of 172 listed. These included 5 supermarkets, 2 butchers/fishmongers/refrigerators, 3 municipal fruit and vegetable markets, 12 small chain markets, 40 local markets, 50 other small retail outlets and 4 bakeries/bakery shops. Results: The results of this study confirmed the consumer profile in society, evaluating food establishments in a city in the interior of Amazonas. It can be concluded that there was a significant reduction in sales of fresh food in establishments in the municipality and a high prevalence of ultra-processed food sales. Conclusion: Therefore, the survey of food environments was extremely important, allowing us to observe that the location and size of establishments influence food choices.